Myeloperoxidase, superoxide dismutase‐3, cardiometabolic risk factors, and distal sensorimotor polyneuropathy: The KORA F4/FF4 study. Issue 5 (6th April 2018) - Herder, Christian; Kannenberg, Julia M.; Huth, Cornelia; Carstensen‐Kirberg, Maren; Rathmann, Wolfgang; Koenig, Wolfgang; Strom, Alexander; Bönhof, Gidon J.; Heier, Margit; Thorand, Barbara; Peters, Annette; Roden, Michael; et al.
Abstract: Background: Oxidative stress has been proposed as important pathomechanism of cardiometabolic diseases and distal sensorimotor polyneuropathy (DSPN). However, the relevance of biomarkers of oxidative stress has not been investigated in this context. Therefore, this study aimed to assess the association of the prooxidant myeloperoxidase (MPO) and the antioxidant extracellular superoxide dismutase (SOD3) with cardiometabolic risk factors and with prevalence and incidence of DSPN. Methods: Cross‐sectional analyses comprised 1069 participants (40.3% with prediabetes and 20.5% with type 2 diabetes) of the population‐based Cooperative Health Research in the Region of Augsburg (KORA) F4 study (2006‐2008), 181 of whom had DSPN at baseline. Prospective analyses included 524 individuals without DSPN at baseline who also participated in the KORA FF4 study (2013‐2014), 132 of whom developed DSPN during the 6.5‐year follow‐up. Serum MPO and SOD3 were measured by ELISA, and their association with cardiometabolic risk factors and DSPN were estimated by using linear and logistic regression analyses. Results: Higher MPO and SOD levels showed multiple positive associations with cardiometabolic risk factors including age, indices of obesity, insulin resistance, serum lipids, renal dysfunction, and biomarkers of inflammation. Higher MPO levels were associated with prevalent DSPN (fully adjusted OR 1.38 [95% CI 1.10; 1.72] per doubling of MPO). Higher baseline SOD3 levels were related to incident DSPN (age and sex‐adjusted OR 2.14 [1.02; 4.48] per doubling of SOD3), which was partially explained by cardiometabolic risk factors. Conclusions: Systemic levels of both pro‐ and antioxidant enzymes appear involved in cardiometabolic risk and development of DSPN.